2010
DOI: 10.3109/07420521003668412
|View full text |Cite
|
Sign up to set email alerts
|

Maximal Power, but Not Fatigability, Is Greater During Repeated Sprints Performed in the Afternoon

Abstract: The present study was designed to investigate if the suggested greater fatigability during repeated exercise in the afternoon, compared to the morning, represents a true time-of-day effect on fatigability or a consequence of a higher initial power. In a counterbalanced order, eight subjects performed a repeated-sprint test [10 x (6 s of maximal cycling sprint + 30 s of rest)] on three different occasions between: 08:00-10:00, 17:00-19:00, and 17:00-19:00 h controlled (17:00-19:00 h(cont), i.e., initial power c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 23 publications
7
37
1
Order By: Relevance
“…These results are consistent with those of Racinais et al (2004Racinais et al ( , 2005Racinais et al ( , 2010 who showed that muscle power is improved in the evening during the RSA test. Moreover, Souissi et al (2004Souissi et al ( , 2007 found that powers during the Wingate and the force-velocity tests fluctuate with time-of-day and reaching its maximum in the evening.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are consistent with those of Racinais et al (2004Racinais et al ( , 2005Racinais et al ( , 2010 who showed that muscle power is improved in the evening during the RSA test. Moreover, Souissi et al (2004Souissi et al ( , 2007 found that powers during the Wingate and the force-velocity tests fluctuate with time-of-day and reaching its maximum in the evening.…”
Section: Discussionsupporting
confidence: 95%
“…Consequently, intermittent training and testing protocols have been proposed to improve soccer players' fitness and guide talent selection (Reilly et al 2000;Impellizzeri et al 2008;Chaouachi et al 2010). In most studies, maximal single or repeated sprint performance has been observed to be higher in the afternoon than in the morning (Racinais et al 2005(Racinais et al , 2010. However, studies of the effects of time-of-day on aerobic metabolism have generally failed to report diurnal variation, especially with intensity near maximal (Dalton et al 1997;Deschenes et al 1998).…”
Section: Introductionmentioning
confidence: 97%
“…The presence of a daily variation in peak velocity in our study disagrees with previous research that reported no such differences (Hamouda et al, 2012;Souissi et al, 2008). Our findings regarding peak power are in agreement with previous research indicating significant diurnal variation in this variable (Aloui et al, 2013;Chtourou et al, 2012;Giacomoni et al, 2006;Hamouda et al, 2012;Racinais et al, 2005Racinais et al, , 2010Souissi et al, 2004Souissi et al, , 2007Souissi et al, , 2008Zarrouk et al, 2012;). However, previous findings regarding peak power are inconsistent.…”
Section: Discussioncontrasting
confidence: 60%
“…Findings from these studies have consistently reported a time-of-day difference for peak power output, with higher values in the mid-afternoon or early evening when compared with the morning ($3.1% to 7.6%) for either the first or first few sprints only (Racinais et al, 2005(Racinais et al, , 2010 or for several sprints (Souissi et al, 2004(Souissi et al, , 2010. The percentage decrement in power over the repeated sprints has also been reported to show diurnal differences Racinais et al, 2005;Zarrouk et al, 2012), with higher decrements in the evening than the morning (4.0-13.1%), although some investigations have not found this result (Hamouda et al, 2012;Souissi et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…A striking difference from our previous study (Portaluppi 2007), was the limited consistency of ''time factors'', which identified only 32 of the 219 references (14.6%) Bougard et al 2009aBougard et al , 2009bCohen et al 2009;Danilenko et al 2009;Di Milia and Bohle 2009;Esquirol et al 2009;Jasper et al 2009;Knadler and Page 2009;Lahiri and Haldar 2009;Larsson et al 2009;Lin HC et al 2009a;Mahoney et al 2009;Minana-Solis et al 2009;Monk et al 2009;Morris et al 2009;Piccione et al 2009;Rosenberg et al 2009;Smith VM et al 2009;Suwazono et al 2009;Terrien et al 2009;van der Leest et al 2009;Vera et al 2009;Werner et al 2009;Wu et al 2009;Ayala and Hermida 2010;Clarisse et al 2010;Greubel et al 2010;Racinais et al 2010;Steinborn et al 2010;Vieira et al 2010). Moreover, using ''time factors'' to search the last 2 years of the MEDLINE with PubMed, 64,626 items were retrieved whose contents were most often unrelated to chronobiology, thus confirming the low specificity of this MeSH term for chronobiologic subjects.…”
Section: Resultsmentioning
confidence: 70%